Asiatic Acid Attenuates Osteoporotic Bone Loss in Ovariectomized Mice Through Inhibiting NF-kappaB/MAPK/ Protein Kinase B Signaling Pathway - Dong, Mingming; Zeng, Jican; Yang, Chenyu; Qiu, Yisen; Wang, Xinjia (Frontiers in Pharmacology, 2022)
Osteoporosis is a condition associated with osteolytic bone disease that is primarily characterized by inordinate osteoclast activation. Protein kinase B (Akt) pathways activated by receptor activator of nuclear factor kappa-B ligand (RANKL) are essential for osteoclastogenesis. Asiatic acid (AA) is a natural pentacyclic triterpenoid compound extracted from a traditional Chinese herb that exhibits a wide range of biological activities. AA has been found to alleviate the hypertrophic and fibrotic phenotype of chondrocytes via the Akt signaling pathway. In this study, we investigated whether AA alleviated bone loss by inhibiting the Akt signaling pathway during osteoclastogenesis and its effect on osteoblasts. The effect of AA cytotoxicity on mouse bone marrow-derived macrophages/monocytes (BMMs) was evaluated in vitro using a Cell Counting Kit-8 assay. The effects of AA on osteoclast differentiation and function were detected using tartrate-resistant acid phosphatase (TRAP) staining and a pit formation assay. A Western blot and qRT-PCR were conducted to evaluate the expression of osteoclast-specific genes and protein signaling molecules. In addition, alkaline phosphatase and alizarin red staining were performed to assess osteoblast differentiation and mineralization. The bone protective effect of AA was investigated in vivo using ovariectomized mice. we found that AA could dose-dependently inhibit RANKL-induced osteoclastogenesis. Moreover, the pit formation assay revealed that osteoclast function was suppressed by treatment with AA. Moreover, the expression of osteoclast-specific genes was found to be substantially decreased during osteoclastogenesis. Analysis of the molecular mechanisms showed that AA could inhibit NF-kappaB/MAPK/Akt signaling pathway, as well as the downstream factors of NFATc1 in the osteoclast signaling pathway activated by RANKL. However, AA did not significantly promote osteoblast differentiation and mineralization. The in vivo experiments suggested that AA could alleviate ovariectomy-induced bone loss in ovariectomized mice. Our results demonstrate that AA can inhibit osteoclastogenesis and prevent ovariectomy-induced bone loss by inhibiting the NF-kappaB/MAPK/Akt signaling pathway. The discovery of the new molecular mechanism that AA inhibits osteoclastogenesis provides essential evidence to support the use of AA as a potential drug for the treatment of osteoclast-related diseases.